Transfer pricing manipulation, tax penalty cost and the impact of foreign profit taxation - Alex A. T. Rathke (ZBW - Leibniz Information Centre for Economics; ZBW - Deutsche Zentralbibliothek für Wirtschaftswissenschaften, Leibniz-Informationszentrum Wirtschaft, 2015)
This paper analyzes the optimal level of transfer pricing manipulation when the expected tax penalty is a function of the tax enforcement and the market price parameter, and the multinational enterprise is subjected to distinct rules of foreign profit taxation. The application of the arm's length principle implies the existence of a range of acceptable prices shaped by market, which influences the probability of tax penalization. It suggests that firms are able to manipulate transfer prices more freely if market price range is wide, or if its delimitations are difficult to determine. Home taxation of foreign profits can reduce income shifting incentive, depending on the portion of repatriation for tax purposes. We find that the limited tax credit rule tends to be a less efficient measure, nonetheless it is the most widely adopted rule by countries, so to spark the perspective of more powerful approaches for taxation of foreign profits.
Keywords: F23; H26; 330; income shifting; transfer pricing manipulation; foreign profit taxation; tax enforcement; Income shifting; Transfer pricing; foreign profit; tax enforcement